Computational study: Windmill-shaped multi-channel SPR sensor for simultaneous detection of multi-analyte. (15th February 2023) - Mumtaz, Farhan; Zhang, Bohong; Roman, Muhammad; Abbas, Lashari Ghulam; Ashraf, Muhammad Aqueel; Dai, Yutang
Highlights: A novel windmill-shaped multi-channel SPR sensor is reported for the detection and quantification of multi-analyte simultaneously. Multi-channel SPR has 3-channels that are used for the detection of chemical and bio-analytes. The maximum wavelength sensitivities of 3, 292 nm/RIU, 6, 664 nm/RIU, and 10, 243 nm/RIU are obtained at the analyte refractive index of 1.34, 1.39, and 1.43 through Ch-1, Ch-2, and Ch-3, respectively. The proposed sensor is being demonstrated for the first time by utilizing the multi-analyte sensing capabilities and high-sensitivity nature. The sensor shows potential for multi-analyte detection without polarization dependency. Abstract: A novel windmill-shaped multi-channel surface plasmon resonance (SPR) sensor for the simultaneous detection and quantification of multi-analyte is reported. The sensor comprises extrinsic multi-channel and is structured as a windmill-shaped structure. Each channel contains a plasmonic Gold (Au) nanowire that induces SPR phenomenon. The sensor has no dependency on polarization, it functions just using y-polarized modes for multi-analyte detection. The maximum wavelength sensitivities of 3, 292 nm/RIU (refractive index unit), 6, 664 nm/RIU, and 10, 243 nm/RIU are obtained at the analyte refractive index (RI) of 1.34, 1.39, and 1.43, with the SPR sensor channel-one (Ch-1), channel-two (Ch-2), and channel-three (Ch-3), respectively. To the best of our knowledge, the proposed windmill-shaped SPR sensor with three extrinsic channels is being demonstrated for the first time by utilizing the multi-analyte sensing capabilities and high-sensitivity nature. The placement of the proposed sensor is anticipated in various potential applications of chemical and bio-analyte detection.